Humanistic Religious Education: Implementing A Pedagogy of Love in The Curriculum For Indonesia’s Young Generation: Pendidikan Agama Humanistik: Menerapkan Pedagogi Cinta dalam Kurikulum Untuk Generasi Muda Indonesia - Setiawan, Muhammad Dicky; Marshanda, Marshanda; Surawan, Surawan (DAS Institute, 2025)
Religious education holds a strategic role in shaping young generations who are religious, ethical, and humanistic. However, the reality of Islamic Religious Education in Indonesia is still dominated by cognitive–doctrinal transmission, leading students to become passive recipients with limited opportunities for critical reflection, empathy, and lived moral experience. This condition demonstrates the need for a paradigmatic shift toward a more liberating, dialogical, and human-centered educational model. This article aims to describe the concept of humanistic religious education by positioning Paulo Freire’s Pedagogy of Love as its philosophical and methodological foundation, and to explain its relevance for curriculum development in Indonesian Islamic education. This research uses a literature review with thematic content analysis. The findings indicate that a Pedagogy of Love serves as a transformative framework that promotes dialogue, empathy, egalitarian teacher–student relations, and critical awareness. It shifts religious education beyond cognitive transfer toward affective–moral formation and social responsibility. Therefore, a Pedagogy of Love-based humanistic approach is essential for strengthening Islamic Religious Education in Indonesia. Future research is recommended to develop operational implementation models so this pedagogical concept can be applied concretely in classroom and madrasah settings.